L'intercompréhension: d'une approche multilingue à une approche plurilingue - Capucho, Filomena (2022)
Intercomprehension (IC) is often presented as the result of learning receptive skills in one or more languages, through the transfer of knowledge and strategies previously acquired or developed. However, the different existing approaches do not exploit all the synergies made possible by an inter-linguistic and inter-textual systematic and simultaneous comparison. Therefore, the IC course certainly becomes, by its structure, a multilingual course, but seldom a plurilingual one. This article tries to show how language learning can effectively benefit from the synergies provided by a real plurilingual approach to IC. This statement will be illustrated through examples provided to the learners by a multinational team of researchers, in the context of the Intermar course.